Integrated ultrafiltration, nanofiltration, and reverse osmosis pilot process to produce bioactive protein/peptide fractions from sardine cooking effluent - Ghalamara, Soudabeh (2022)
Sardine cooking effluents contain a high level of organic matter, such as proteins and lipids, which allows them to be forward into a chain exploiting high added-value compounds attained from these effluents, increasing their economic value while reducing their environmental effect. Thus, the purpose of this work was to develop an innovative pilot-scale integrated membrane process, with or without enzymatic hydrolysis, to obtain fractions with high protein/peptide and low NaCl contents, as well as optimized bioactive properties. The research strategy followed involved the use of ultrafiltration (UF) and nanofiltration (NF) technologies of the pretreated sardine cooking effluent followed by reverse osmosis (RO) at a pilot scale levels. Moreover, it allowed for the attainment of fractions rich in protein/peptides that might be used in the food, pharmaceutical, or cosmetic industries, particularly after RO, as they present a lower NaCl content. The RO retentate (hydrolyzed sample) coupled with UF and NF resulted in the fractions with the best bioactive properties (higher antioxidant capacity and antimicrobial activity) of all the analyzed samples. Overall, the current work demonstrated the feasibility of exploiting liquid by-products as a source of functional components as well as reinforcing this strategy’s potential relevance in future effective management strategies for this type of effluents.